2007
DOI: 10.1002/dneu.20386
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in zebrafish lateral line neuromasts: Expression of the neural progenitor cell marker sox2 and proliferation‐dependent and‐independent mechanisms of hair cell renewal

Abstract: Mechanosensory hair cells are essential for audition in vertebrates, and in many species, have the capacity for regeneration when damaged. Regeneration is robust in the fish lateral line system as new hair cells can reappear after damage induced by waterborne aminoglycoside antibiotics, platinum-based drugs, and heavy metals. Here, we characterize the loss and reappearance of lateral line hair cells induced in zebrafish larvae treated with copper sulfate using diverse molecular markers. Transgenic fish that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 49 publications
6
162
0
Order By: Relevance
“…1G and Fig. S1) (40). Counts of Sox2 + FACS-purified cells revealed that 95% of GFP + cells but only 6.6% of GFP − cells were positive for Sox2 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…1G and Fig. S1) (40). Counts of Sox2 + FACS-purified cells revealed that 95% of GFP + cells but only 6.6% of GFP − cells were positive for Sox2 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Neuromasts exposed to copper showed both mitotic and nonmitotic regeneration depending on the severity of damage (Hernandez et al, 2007). Exposure of 3 dpf larvae to 1 M CuSO 4 resulted in mostly nonmitotic renewal, although treatment with a higher concentration (10 M) resulted in mostly proliferative replacement (Hernandez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of 3 dpf larvae to 1 M CuSO 4 resulted in mostly nonmitotic renewal, although treatment with a higher concentration (10 M) resulted in mostly proliferative replacement (Hernandez et al, 2007). There are several possibilities to explain the differences in the level of nonmitotic regeneration after low-dose copper compared with that seen after high copper or with neomycin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live 5-dpf WT and mutant Et(krt4:GFP) sqet4 larvae were immersed in 5 M CuSO4 in E3 medium (18) for 1 h at 28.5°C and then rinsed twice briefly in E3 medium. After confirming essentially complete hair-cell death in the lateral line by fluorescence microscopy, we allowed treated animals to recover in E3 medium at 28.5°C.…”
Section: Fluorophore Labeling Of Hair Cells and Electrical Recordingsmentioning
confidence: 99%